An integer linear programming approach to the travelling salesman problem for optimizing self-drive tourist routes in Kuala Lumpur / Nur Azirah Suliman … [et al.] - Suliman, Nur Azirah; Mohd Yusop, Noorezatty; Mat Janggi, Nurfaqihah Athirah; Kamaruddin, Nur Shamira Shamimi; Mohd Basir, Nora (Universiti Teknologi MARA, Perak, 2024)
Self-drive tourism offers tourists the flexibility to explore destinations at their own pace, utilizing private transport. However, it is essential to underscore the significance of thorough planning for a successful and enjoyable experience. The objective of this research is to explore the concept of travelling salesman problem and its application in optimizing travel routes for self-drive tourists visiting Kuala Lumpur. The study employed an Integer Linear Programming (ILP) model to propose efficient routes that connect all seven notable points of interest in Kuala Lumpur, including the Petronas Twin Towers, Batu Caves, Central Market, Merdeka Square, Bukit Bintang, KL Tower, and Titiwangsa Lake Garden. Implementation of ILP for suggested routes results in a reduction of approximately 36.86% in transportation distance, ultimately leading to a decrease in transportation costs. This demonstrates the effectiveness and efficiency of the proposed approach, enabling tourists to maximize their experience while minimizing time and energy spent navigating congested or inefficient roads. This research emphasizes the importance of self-drive tourism and the application of an ILP model in optimizing travel routes for tourists in Kuala Lumpur. By following the suggested routes, visitors can efficiently navigate the city's diverse neighborhoods and transportation options, while enjoying its notable attractions. The significant reduction in transportation distance achieved through this approach highlights its effectiveness in enhancing the travel experience in Kuala Lumpur.